Genome-wide analysis of epigenetic and transcriptional changes in the pathogenesis of RGSV in rice - Wu, Xiaoqing; Liu, Hongfei; Lian, Bi; Jiang, Xue; Chen, Cheng; Tang, Tianxin; Ding, Xinlun; Hu, Jie; Zhao, Shanshan; Zhang, Shuai; Wu, Jianguo (Frontiers in Plant Science, 2023)
Rice grassy stunt virus (RGSV), a typical negative single-stranded RNA virus, invades rice and generates several disease signs, including dwarfing, tillering, and sterility. Previous research has revealed that RGSV-encoded proteins can force the host’s ubiquitin-proteasome system to utilize them for viral pathogenesis. However, most of the studies were limited to a single omics level and lacked multidimensional data collection and correlation analysis on the mechanisms of RGSV-rice interactions. Here, we performed a comprehensive association analysis of genome-wide methylation sequencing, transcriptome sequencing, and histone H3K9me3 modification in RGSV-infested as well as non-infested rice leaves, and the levels of all three cytosine contexts (CG, CHG and CHH) were found to be slightly lower in RGSV-infected rice leaves than in normal rice. Large proportions of DMRs were distributed in the promoter and intergenic regions, and most DMRs were enriched in the CHH context, where the number of CHH hypo-DMRs was almost twice as high as that of hyper-DMRs. Among the genes with down-regulated expression and hypermethylation, we analyzed and identified 11 transcripts involved in fertility, plant height and tillering, and among the transcribed up-regulated and hypermethylated genes, we excavated 7 transcripts related to fertility, plant height and tillering. By analyzing the changes of histone H3K9me3 modification before and after virus infestation, we found that the distribution of H3K9me3 modification in the whole rice genome was prevalent, mainly concentrated in the gene promoter and gene body regions, which was distinctly different from the characteristics of animals. Combined with transcriptomic data, H3K9me3 mark was found to favor targeting highly expressed genes. After RGSV infection, H3K9me3 modifications in several regions of CTK and BR hormone signaling-related genes were altered, providing important targets for subsequent studies.